Filling the gap: brief neuropsychological assessment protocol for glioma patients undergoing awake surgeries - Ohy, Juliana Bastos; Formentin, Cleiton; Gripp, Daniel Andrade; Nicácio Jr, Joab Alves; Velho, Maíra Cristina; Vilany, Larissa Núbia; Greggianin, Gabriel Frizon; Sartori, Beatriz; Campos, Ana Carolina Pinheiro; Verst, Silvia Mazzali; Maldaun, Marcos Vinicius Calfat (Frontiers in Psychology, 2024)
Introduction The literature lacks a concise neurocognitive test for assessing primary cognitive domains in neuro-oncological patients. This study aims to describe and assess the feasibility of the Ohy-Maldaun Fast Track Cognitive Test (OMFTCT), used to pre- and post-operatively evaluate patients undergoing brain tumor surgery in language eloquent areas. The cognitive diagnosis was used to safely guide intraoperative language assessment. Methods This is a prospective longitudinal observational clinical study conducted on a cohort of 50 glioma patients eligible for awake craniotomies. The proposed protocol assesses multiple cognitive domains, including language, short-term verbal and visual memories, working memory, praxis, executive functions, and calculation ability. The protocol comprises 10 different subtests, with a maximum score of 50 points, and was applied at three time points: preoperative, immediately postoperative period, and 30 days after surgery. Results Among the initial 50 patients enrolled, 36 underwent assessment at all three designated time points. The mean age of the patients was 45.3 years, and they presented an average of 15 years of education. The predominant tumor types included Glioblastoma, IDH-wt (44.1%), and diffuse astrocytoma, IDH-mutant (41.2%). The tumors were located in the left temporal lobe (27.8%), followed by the left frontal lobe (25%). The full test had an average application time of 23 min. Conclusion OMFTCT provided pre- and postoperative assessments of different cognitive domains, enabling more accurate planning of intraoperative language testing. Additionally, recognition of post-operative cognitive impairments played a crucial role in optimizing patient care.